Tujuh Faktor Utama Keberhasilan Peserta Didik Dalam Memahami Mata Pelajaran Aqidah Akhlak - Busthomi, Yazidul (PT. Sharia Journal and Education Center, 2024)
Abstract During this period, there is a need for good habits in children and the cultivation of good and correct aqidah, because at an early age a child is like white paper that is not stained, and this must be maintained with good habits, and parents have an important role in the child himself. Education and development of faith and morals should be done from an early age, but that does not mean that education and development of faith and morals are not needed when people are adults. Education and development of faith and morals must continue to be carried out because education on faith and morals is lifelong until the end of life. The seven main factors for students' success in understanding the subject of moral aqidah are as follows: 1. Students have a high level of intelligence, 2. Students have motivation in learning, 3. Students are interested in learning, 4. Students are always healthy, 5. Students behave well, 6. Students receive attention from their parents, 7. Teachers use appropriate methods for students. Keywords: Main factors, students, moral aqidah Abstrak Dalam masa ini, diperlukan adanya pembiasaan yang baik pada diri anak dan penanaman aqidah yang baik dan benar, karena pada usia dini seorang anak bagaikan kertas yang putih yang tidak ternoda, dan ini harus dijaga dengan pembiasaan yang baik, dan orang tua memiliki peran penting pada diri anak tersebut. Pendidikan dan pengembangan akidah dan akhlak, selayaknya memang dilakukan sejak anak masih berusia dini, namun bukan berarti pendidikan dan pengembangan akidah dan akhlak tidak diperlukan ketika orang sudah dewasa. Pendidikan dan pengembangan akidah dan akhlak harus tetap dilakukan karena pendidikan akidah dan akhlak ini bersifat sepanjang masa sampai akhir hayat. Tujuh faktor utama keberhasilan peserta didik dalam memahami mata pelajaran aqidah akhlak yaitu sebagai berikut: 1. Peserta didik tingkat kecerdasannya tinggi, 2. Peserta didik mempunyai motivasi dalam belajar, 3. peserta didik berminat dalam belajar, 4. Peserta didik selalu sehat, 5. Peserta didik bersikap yang baik, 6. Peserta didik mendapat perhatian dari orangtuanya, 7. Guru menggunakan metode yang sesuai kepada peserta didik. Kata kunci: Faktor utama, Peserta didik, Aqidah akhlak